Analisis Kapasitas Produksi Steel and Fire Door dalam Penyusunan Master Production Schedule Menggunakan Metode Rough Cut Capacity Planning - Muhammad Yusuf Sholahuddin Ansori; Renanda Nia Rachmandita; Thina Ardliana (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
PT. AAM Surabaya implements MTO and Jobshop strategies. Some of the steel and fire door projects were delayed. One of the factors is MPS was arranged without considering the production capacity. It is necessary to calculate the production capacity as a reference in the preparation of MPS. This study uses RCCP method to calculate production capacity. Preparation of MPS by using transportation method taking into account the results of RCCP analysis. Production scheduling is also performed to one of the project have the biggest delay using shortest processing time (SPT) rules with WinQSB software. The results of this study obtained the calculation of available capacity and needed capacity uses in analysis of production capacity feasibility, there were 6 projects that met the target and 9 projects didn't meet the target. Based on the results, MPS preparation was conducted by determining how long regular hours and overtime using transportation methods, total cost of overall machinery using transportation methods is Rp. 1,344,723,150,-. While the company's cost Rp. 1,581,390,000,. Production scheduling on MIS-DSD project is faster completion times than the company's plans. The company's scheduling is 22 days effective while using WinQSB software is 19 days effective. The result of this research can be used as a reference by PT. AAM Surabaya in the next production to minimize the occurrence of delays.